Número 21 (La Lupa. Colección fueguina de divulgación científica, 2025)
COMITÉ EDITORIAL Editora responsableMaría Paz MartinoliEditores asistentesJimena Elizabeth ChavesDamián A. FernándezMauricio González GuillotCecilia Inés GutiérrezMaría Constanza Maluendez TestoniVictoria Mosqueira GonzálezPaula RodríguezFernando C. SantiagoAsesores informáticosFernando GiniRodrigo Leandro GaunaColaboradoresJulia TiltonHenry HoddeFacundo SotaDiseño y DiagramaciónIrina Castro PeñaUshuaia, Tierra del Fuego, ArgentinaInstagram: @disenioalsurImpresiónM&A Diseño y Comunicación S.R.L.Buenos Aires, ArgentinaE-mail: info@myaweb.com.ar